Response—Werner F. Grunbaum - Werner F. Grunbaum (Washington University Law Quarterly, 1971)
social science has important contributions to make to the law in all of these areas. However, applied research must be supplemented by significant basic theoretical research. Applied research without substantive theoretical base will lead sooner or later to the same condemnation of "infant social science" that was voiced in connection with the Brown v. Board decision. Problem oriented social science research cannot and will not endure unless it is grounded in sound basic theoretical research. Although this criticism is not applicable to the contributions in this symposium, if the present trend emphasizing policy oriented research continues, it will be only a matter of time before policy oriented research enters a state of decline. Therefore, it is regrettable that the present symposium fails to strike a balance between policy oriented research and basic theoretical studies.